Analisis Struktur Ekonomi dan Sektor Unggulan Kabupaten Aceh Besar - Irwan Safwadi; Marah Sutan Rangkuti (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
Development policy through the optimization of local resource potential is a need that needs to be prepared in order to encourage the acceleration of regional economic growth. Identify changes in economic structure and determine the leading economic sectors including one of the efforts to accelerate the process of achieving economic growth. This study aims to analyze changes in economic structure and determine the leading economic sectors in Aceh Besar District. The data used is secondary data in the form of time series data (time series) Gross Regional Domestic Product (GRDP) of Aceh Besar Regency based on constant prices and GRDP of Aceh Province based on the constant price of 2012-2016. The analyzer used is Shift-Share. During the last five years, Aceh Besar's economic structure based on Shift-Share was only donated by Aceh Province by 19.60 percent. Furthermore, the industry mix contributed 17.89 percent. The leading economic sectors accounted for 62.50 percent of Aceh Besar economic structure changes. The result of Shift Share analysis shows that most of Aceh Besar Regency's economic sector is one of the leading sectors that grow fast in economy in Aceh Province. Only the electricity and gas procurement sector does not excel in Aceh Besar.